1998
DOI: 10.1063/1.120988
|View full text |Cite
|
Sign up to set email alerts
|

Spin relaxation of excitons in zero-dimensional InGaAs quantum disks

Abstract: We report the observation of spin relaxation of excitons in zero-dimensional semiconductor nanostructures. The spin relaxation is measured in InGaAs quantum disks by using a polarization dependent time-resolved photoluminescence method. The spin relaxation time in a zero-dimensional quantum disk is as long as 0.9 ns at 4 K, which is almost twice as long as the radiative recombination lifetime and is considerably longer than that in quantum wells. The temperature dependence of the spin relaxation time suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
47
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 16 publications
13
47
3
Order By: Relevance
“…The emission from peak 1 was also linearly polarized. Since the degree of polarization of the emission depended strongly on the pump polarization angle, we believe that the effect is largely due to the selection rules for photon absorption and emission [20,21]. The polarization of a pump photon is transferred into the spin of an exciton, and if no spin relaxation occurs, the spin is transfered back to the emitted photon polarization.…”
mentioning
confidence: 99%
“…The emission from peak 1 was also linearly polarized. Since the degree of polarization of the emission depended strongly on the pump polarization angle, we believe that the effect is largely due to the selection rules for photon absorption and emission [20,21]. The polarization of a pump photon is transferred into the spin of an exciton, and if no spin relaxation occurs, the spin is transfered back to the emitted photon polarization.…”
mentioning
confidence: 99%
“…These expectations have been reinforced by numerous experimental confirmations of long spin relaxation times reported for carriers in the ground state of a QD at low temperatures. 5,6 Unfortunately, experimental investigations of spin properties of QDs at room temperature ͑RT͒, relevant to practical device applications, still remain sparse. Reported values of RT electron spin polarization, by monitoring optical polarization in continuous-wave ͑cw͒ optical orientation or electrical injection experiments, have so far been largely limited to just a few percent.…”
mentioning
confidence: 99%
“…4,5,6,7 Recent studies of electron spin dynamics in neutral QDs 4,5,8 have revealed that the discrete energy levels in quantum dots arising from three-dimensional quantum confinement blocks the dominant spin relaxation channels present in higher dimensional bulk and quantum well systems, resulting in considerably longer spin relaxation times. Combined with the high optical luminescence efficiency observed in QDs, 9,10,11 these long spin relaxation times should lead to larger spin-dependent luminescence signatures in spin detection applications incorporating QDs as an optical marker.…”
mentioning
confidence: 99%